2017
DOI: 10.1590/1982-0224-20160170
|View full text |Cite
|
Sign up to set email alerts
|

A macroscopic classification of the embryonic development of the one-sided livebearer Jenynsia multidentata (Teleostei: Anablepidae)

Abstract: This study proposes eight stages according to the main discernible changes recorded throughout the embryonic development of Jenynsia multidentata. The development of morphological embryo structures, pigmentation, and changes in tissues connecting mother and embryo were included in the stage characterization. From the fertilized egg (Stage 1), an embryo reaches the intermediary stages when presenting yolk syncytial layer (Stage 2), initial pigmentation of the outer layers of the retina and dorsal region of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…While prior studies have mentioned the presence of a branchial placenta of J. lineata and describe some morphological aspects (Schindler & de Vries, 1988;Turner, 1940;Wourms et al, 1988), this is the first work where its morphology is analyzed in conjunction with histochemical changes and cell proliferation. The current study revealed the presence of the branchial placenta in ovaries corresponding to gestational stages 6-8 (López-Rodríguez et al, 2017). In each of them, ovarian branches were observed to penetrate the embryonic opercular clefts in apposition with the developing gill, forming a branchial placenta.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…While prior studies have mentioned the presence of a branchial placenta of J. lineata and describe some morphological aspects (Schindler & de Vries, 1988;Turner, 1940;Wourms et al, 1988), this is the first work where its morphology is analyzed in conjunction with histochemical changes and cell proliferation. The current study revealed the presence of the branchial placenta in ovaries corresponding to gestational stages 6-8 (López-Rodríguez et al, 2017). In each of them, ovarian branches were observed to penetrate the embryonic opercular clefts in apposition with the developing gill, forming a branchial placenta.…”
Section: Discussionmentioning
confidence: 55%
“…In the 15 ovaries observed in pregnant females, the entire ovarian lumen was found dilated and occupied by 10–21 embryos, arranged parallel to the longitudinal axis of the organ. All embryos were assigned to gestational stages 6–8 according to López‐Rodríguez et al (2017). Therefore, the ovarian follicles were observed only in the cephalic portion and were characterized by being scarce, small in size, and found in the first stages of follicular development.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations